Effectiveness of simulation learning methods on improving the clinical skills of nursing students in midwifery care - Andi Suriyani; Darmi Arda; Ismarulyusda Ishak (Edukasi Ilmiah Indonesia, 2025)
Introduction: Clinical competence is a crucial component of nursing education, particularly in midwifery care, where students must integrate knowledge, technical skills, and decision-making to ensure the safety of both mothers and newborns. Traditional classroom learning often fails to provide sufficient opportunities for hands-on experience. Simulation-based learning has emerged as an innovative pedagogical approach to enhance clinical competence in a safe and controlled environment. This study aimed to evaluate the effectiveness of simulation learning methods in improving the clinical skills of nursing students in midwifery care. Methods: A quasi-experimental pre–post design was conducted among 80 nursing students enrolled in a midwifery course. The intervention group participated in a structured simulation learning program involving high-fidelity obstetric manikins and scenario-based training on antenatal, intrapartum, and postpartum care. The control group received conventional lectures and demonstrations. Data were collected using an Objective Structured Clinical Examination (OSCE) checklist and a self-efficacy questionnaire before and after the intervention. Paired and independent t-tests were used to analyze changes in clinical skill scores and confidence levels. Results: The findings revealed a significant improvement in the clinical performance of students in the simulation group (mean score increase from 68.4 ± 7.2 to 86.7 ± 6.5; p < 0.001) compared to the control group (72.1 ± 8.0 to 75.8 ± 7.6; p = 0.054). Students also reported enhanced confidence and readiness for real clinical practice. Conclusion: Simulation-based learning effectively improves clinical skills and self-efficacy in midwifery education. Integration of simulation into nursing curricula can bridge the gap between theory and practice, ensuring better preparedness for clinical settings.